Productivity of selection numbers of perennial ryegrass (Lolium perenne L.) in the nursery of competitive variety testing - Volodymyr Oleksiak; Lesia Baistruk-Hlodan; Oleg Stasiv; Hryhorij Konyk (Наукові горизонти)
Increasing the efficiency of perennial ryegrass cultivation is possible by improving breeding work and clear organisation of seed production, as the variety plays a decisive role in this process. The purpose of this study was to evaluate promising perennial ryegrass material for productivity in haymaking and pasture use and to select the best numbers for submission for scientific and technical expertise. The study was conducted during 2022-2024 at the Precarpathian Research Department of the Institute of Agriculture of the Carpathian Region of NAAS (Drohobych district, Lviv region). The selection of breeding material and phenological observations were performed following the “Methodology for breeding perennial legumes and cereals in the Carpathian region” (2015) and “Formation and conservation of genetic diversity of forage and lawn grasses in the Carpathian region” (2015). In the competitive variety trial for haymaking, 2 selection numbers of perennial ryegrass (PFZ 02082 and PFZ 02514) were distinguished by plant height; 4 numbers – by leafiness (PFZ 02082; PFZ 02136; PFZ 02320; PFZ 02514), 2 numbers (PFZ 02082; PFZ 02514), 2 numbers – by green mass yield (PFZ 02082; PFZ 02514), and 2 numbers (PFZ 02082; PFZ 02514) – by dry matter yield. Under the pasture method of use, the best were the numbers PFZ 02082 and PFZ 02514 in terms of plant height, PFZ 02082; PFZ 02081 and PFZ 02514 in terms of leafiness, PFZ 02082; PFZ 02081; PFZ 02514 in terms of green mass yield, and PFZ 02082; PFZ 02081; PFZ 02514 in terms of dry matter yield. The highest seed yields were provided by PFZ 02082; PFZ 02136; PFZ 02081; PFZ 02514 (0.41 t/ha, 0.39 t/ha, 0.37 t/ha, and 0.35 t/ha). The promising numbers PFZ 02082 and PFZ 02514 for hayfield and pasture use were identified, which will be submitted to the State Scientific and Technical Expertise after multiplication